HUBUNGAN PERSEPSI IBU TENTANG MUTU PELAYANAN DENGAN MINAT PEMANFAATAN ANTENATAL CARE DI PUSKESMAS PADANGSARI - Vivin Fitria Anggraeni; Anneke Suparwati; Ayun Sriatmi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
ANC service at Primary Health Center of Padangsari Semarang city is still far from expectations due to the persistence of disinterest pregnant women to the examination of the ANC that felt takes a long time, the officer is less thorough when doing the inspection, and giving an explanation of the action the inspection did not detail. ANC quality standards are seen from 5 quality dimension such as reliability, responsiveness, assurance, empathy, and tangible. Goal achievement of ANC is measured by how much interest to visit ANC in health center. The aim of this research is to measure the perception about ANC quality with interest to use ANC service in Health Center of Padangsari. The method of this research was using Explanatory Research with Cross Sectional approach. The population in this research was 82 peoples with 50 peoples as sample research. The analysis of the data was using univariate and bivariate analysis with Chi Square Test. The results show that the perception of reliability has relationship with the interest in ANC utilization (p-value = 0.005). Perception of responsiveness has relationship with the interest in ANC utilization (p-value = 0.000). Perception of insurance has relationship with the interest in ANC utilization (p-value = 0.000). Perception of empathy has a relationship with the interest in ANC utilization (p-value = 0.000). Perception of tangible has relationship with the interest in ANC utilization (p-value = 0.000). Based on these results, it is necessary to improve the quality inspection 10T, ANC service speed, ANC clear examination result, and encouragement for regular inspection.